Phytochemicals from Edible Flowers Prevent Neurodegenerative Diseases Via the Gut-Brain Axis - Echeverria-Morgado, J (Elsevier Ltd, 2025)
The gut-brain axis is a complex bidirectional communication network between the gastrointestinal tract and the central nervous system (CNS). The axis is crucial in maintaining overall health and well-being which influences various physiological processes, including digestion, metabolism, immune system, and cognitive/emotional functions. Dysregulation of the gut-brain axis has been implicated in the development of neurodegenerative diseases (NDDs). While there are limited conventional treatments for these conditions, an increasing interest in exploring natural and dietary interventions may offer neuroprotective benefits. The present study explores the neuroprotective effects of edible flower phytochemicals on the gut-brain axis, shedding light on their therapeutic applications and highlighting the need for further research. This study helps to fully understand the role of edible flower phytochemicals in promoting neuroprotection through the gut-brain axis. Studies were identified through a systematic and comprehensive search of ScienceDirect, PubMed, and Scopus databases. Eligibility checks were conducted based on predefined selection criteria. Directly 25 articles were included in this study and based on the authors expertise and reference list of included studies several other related articles were used. Edible flowers are rich sources of bioactive compounds such as phenolic compounds, carotenoids, alkaloids, and terpene/terpenoids. Edible flower bioactive compounds have been valued in traditional medicine for centuries considering their potential health benefits including anti-inflammatory, antioxidant, and neuroprotective effects. Edible flowers have the potential to combat NDDs by modulating the gut-brain axis and harnessing the neuroprotective properties of their bioactive compounds. © 2024